Brand Awareness and Sustainability in Shaping Promotion Strategies in Indonesia - Rachmawati, Erny; Akbar, Hammad (Jurnal Manajemen Bisnis, 2025)
Research aims: This study aims to investigate the impact of service quality, brand awareness, consumer experience, and environmental sustainability on brand image and brand advocacy in Indonesia. It seeks to determine the extent to which these factors influence brand image and how brand image mediates their effect on brand advocacy.Design/Methodology/Approach: A quantitative research methodology was adopted, involving the collection of data from 300 respondents in Indonesia. Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) was employed to analyze the relationships between the variables. Research findings: The findings reveal that service quality, brand awareness, consumer experience, and environmental sustainability significantly influence brand image, which in turn strongly impacts brand advocacy. Consumer experience has the greatest effect, followed by service quality, brand awareness, and environmental sustainability. While these insights are valuable for the Indonesian market, expanding the study’s geographic or sectoral scope could provide a broader understanding of brand perception and advocacy across diverse cultural and economic contexts, enhancing its global applicability. Theoretical Contribution/Originality: This research contributes to the literature on branding by offering empirical evidence on the combined impact of service quality, brand awareness, consumer experience, and environmental sustainability on brand image and advocacy in the Indonesian context. It underscores the mediating role of brand image in strengthening consumer advocacy. Practitioners/Policy Implications: For practitioners, the study provides practical insights into how companies can enhance brand image and foster consumer advocacy by improving service quality, raising brand awareness, enhancing consumer experience, and promoting environmental sustainability. This is particularly relevant for businesses in Indonesia aiming to build strong brands and loyal customer base. Research Limitations/Implications: The study is limited to a single country (Indonesia) and specific sectors, which may limit the generalizability of the findings to other regions or industries. Future research could explore additional variables or investigate the effects in other cultural or geographical settings.